Training and development as a tool for improving basic service delivery; the case of a selected municipality - Mthokozisi Mpofu; Clifford Kendrick Hlatywayo (Journal of Economics, Finance and Administrative Science, 2015)
Municipal employees have come under fire for poor performance and conduct in their work as some engage in corruption and others are not qualified enough to discharge their duties to the required levels. Employee training and development has become one of the key aspects in improving employee performance in organisations, thus leading to improved organizational performance and growth. The study investigated the relationship between the quality of employee training and development on service delivery in a selected municipality with data collected from 150 employees. The results indicated the need for effective employee training and development systems and processes to achieve improved employee performance thus improved provision of basic services to the communities. – – Los empleados municipales han sufrido despidos debido al bajo rendimiento de su trabajo, ya que muchos de ellos caen en corrupción y otros no están lo suficientemente calificados para cumplir con sus obligaciones en el nivel requerido. La formación y desarrollo del personal se ha convertido en uno de los aspectos clave para mejorar su desempe\~no en las organizaciones y lograr el mayor rendimiento y crecimiento de estas. El estudio investigó la relación entre la calidad de la formación y el desarrollo del personal y la dotación de servicios en un municipio seleccionado, recogiendo información de 150 empleados. Los resultados mostraron la necesidad de contar con sistemas y procesos de formación y desarrollo del personal, para el logro de una mejora de su desempe\~no, lo que redunda en una mejor dotación de servicios básicos a las comunidades.
Keywords: G14; 330; Employee training and development; Service delivery; Formación y desarrollo de los empleados; Dotación de servicios